ANALISIS KESUKSESAN SIAKAD MENGGUNAKAN METODE DELONE AND MCLEAN IS SUCCESS MODEL PADA ITBSS - Melyanto Melyanto (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Information Technology has penetrated various fields, including education. As a higher education in West Kalimantan, Institut Teknologi dan Bisnis Sabda Setia (ITBSS has implemented an Academic Information System (SIAKAD) for students. SIAKAD aims to facilitate students in accessing academic information online throughout their studies. However, ITBSS never conduct an analysis of SIAKAD usage since its initial implementation. This analysis should be executed to measure the success of SIAKAD usage, ensuring that the investment in SIAKAD is effective. This study aims to analyze the success of SIAKAD at ITBSS using the DeLone & McLean IS Success Model (D&M IS Success Model) by examining the relationships between the model’s variables: system quality, information quality, service quality, user satisfaction, and net benefits.This model is a widely adopted model among researchers for analyzing the success of information system implementations across various institutions. The results of this study indicated a positive relationship between system quality, information quality, and service quality with user satisfaction, as well as a positive relationship between user satisfaction and benefits. These findings provided a evidence for ITBSS to focus on enhancing the system, information, and service quality aspects of SIAKAD to improve user satisfaction and foster positive perceptions of its benefits.